2008
DOI: 10.1017/s0007114507853323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incremental levels of sunflower-seed oil in the diet on ruminal lipid metabolism in lactating cows

Abstract: Based on the potential benefits of cis-9,trans-11-conjugated linoleic acid (CLA) for human health there is interest in developing sustainable nutritional strategies for enhancing the concentration of this fatty acid in ruminant-derived foods. Most evidence to date suggests that endogenous synthesis is the major source of cis-9,trans-11 in milk fat and ruminal outflow is limited and largely independent of dietary 18 : 2n-6 supply. Four lactating cows fitted with a rumen cannula were used in a 4 £ 4 Latin square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
122
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(147 citation statements)
references
References 59 publications
19
122
2
4
Order By: Relevance
“…Fish oil or marine algal oil rich in long chain polyunsaturated fatty acids (PUFA) in the diet are known to inhibit the complete biohydrogenation of C18 unsaturated fatty acids resulting in an increase in ruminal trans 18:1 and trans 18:2 outflow Kim et al, 2008;Lee et al, 2008). Incubations with rumen micro-organisms have shown that eicosapentaenoic acid (EPA; cis-5, cis-8, cis-11, cis-14, cis-17 20:5) and docosahexaenoic acid (DHA; Figure 2 Putative pathways describing cis-9, cis-12 18:2 metabolism in the rumen (adapted from Harfoot and Hazlewood, 1988;Hudson et al, 1998;Wallace et al, 2007;Shingfield et al, 2008a). Arrows with solid lines highlight the major biohydrogenation pathway, whereas arrows with dashed lines describe the formation of minor fatty acid metabolites.…”
Section: Ruminal Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish oil or marine algal oil rich in long chain polyunsaturated fatty acids (PUFA) in the diet are known to inhibit the complete biohydrogenation of C18 unsaturated fatty acids resulting in an increase in ruminal trans 18:1 and trans 18:2 outflow Kim et al, 2008;Lee et al, 2008). Incubations with rumen micro-organisms have shown that eicosapentaenoic acid (EPA; cis-5, cis-8, cis-11, cis-14, cis-17 20:5) and docosahexaenoic acid (DHA; Figure 2 Putative pathways describing cis-9, cis-12 18:2 metabolism in the rumen (adapted from Harfoot and Hazlewood, 1988;Hudson et al, 1998;Wallace et al, 2007;Shingfield et al, 2008a). Arrows with solid lines highlight the major biohydrogenation pathway, whereas arrows with dashed lines describe the formation of minor fatty acid metabolites.…”
Section: Ruminal Lipid Metabolismmentioning
confidence: 99%
“…Arrows with solid lines highlight the major biohydrogenation pathway, whereas arrows with dashed lines describe the formation of minor fatty acid metabolites. cis-9,trans-11, cis-15 18:3 cis-9, cis-12, cis- Figure 3 Putative pathways describing cis-9, cis-12, cis-15 18:3 metabolism in the rumen (adapted Harfoot and Hazlewood, 1988;Destaillats et al, 2005;Wą sowska et al, 2006 andShingfield et al, 2008a). Arrows with solid lines highlight the major biohydrogenation pathway, whereas arrows with dashed lines describe the formation of minor fatty acid metabolites.…”
Section: Ruminal Lipid Metabolismmentioning
confidence: 99%
“…Supplements of PUFA typically modify rumen fermentation, characterized by a shift toward propionate at the expense of acetate, butyrate, or both lipogenic VFA (Ueda et al, 2003;Hurtaud and Peyraud, 2007;Shingfield et al, 2008a). Changes in molar VFA proportions to plant oils may be related to the toxic effects of LA and ALA on specific cellulolytic and butyrate-producing bacteria (Maia et al, 2007;Yang et al, 2009).…”
Section: Rumen Fermentation and Nutrient Digestibilitymentioning
confidence: 99%
“…Such findings are consistent with a finite capacity for FA absorption in the small intestine of lactating cows ) that may be related to the saturation of 18:0 intestinal absorption at high postruminal flows . In cows fed grass silage or RCS diets, 18:0 is typically the major FA leaving the rumen (Shingfield et al, 2008a(Shingfield et al, , 2012Halmemies-Beauchet-Filleau et al, 2013b).…”
Section: Continuedmentioning
confidence: 99%
“…Ruminal effects of feeding up to 500 g/day of plant oils have been small (e.g. Shingfield et al, 2008), but strong adverse effects of fat supplementation on NDF digestibility and rumen NDF turnover were observed at high levels (67 g/kg diet DM) of rapeseed oil supplementation in cattle fed a grass silagebased diet (Tesfa, 1993). The slopes of concentrate ME concentration on SDMI were similar in studies investigating the effects of concentrate carbohydrate composition and fat supplementation (20.386 and 20.374 kg DM/MJ ME per kg DM increase in concentrate ME).…”
Section: Concentrate Supplementationmentioning
confidence: 99%